Pendampingan Praktek Budidaya Maggot Sebagai Sumber Protein Pakan Ayam Buras - Tamzil, Mohammad Hasil; Indarsih, Budi; Jaya, I Nyoman Sukartha; Haryani, Ni Ketut Dewi (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This community service aims to provide additional knowledge and skills about the maggot cultivation system to members of the Istiqomah Dasan Cermen chicken farmer group, Sandubaya, Mataram city. This activity was held through collaboration between members of the Istiqomah chicken farmer group and the Community Service Team of the Faculty of Animal Husbandry, University of Mataram. Community service activities were carried out using lecture methods, discussions, implementation of practices and direct inspections of group cages. The materials provided were the breeding system, maggot egg hatching, maggot rearing and maggot harvesting. All series of activities went smoothly, and all participants followed carefully. Through this activity, all members of the Istiqomah chicken farmer group gained additional knowledge and skills about the maggot production system for chicken feed. It can be concluded that this community service activity went smoothly and met the targets and objectives.